Social Media and Gender Equality: Knowledge, Attitude and Practice - Bello, Abidemi; Irele, Abigail Olubukola (The Gender Truth Journal, 2025)
Issues of gender representation and visibility on various social media platforms and access to specific roles, responsibilities, tasks, and privileges, as well as gender portrayal, have been on the international agenda since the 1990s, raising concerns about news media diversity and accessibility. Construction of gender goes on today through various technologies and individual discourses with the power to control the field of social meaning and thus produce, promote, and ‘implant’ representations of gender. Therefore, this study examined the influence of social media on the knowledge, attitude, and practice of gender equality among residents of Oyo State. The study is anchored on Technological Determinism Theory. The study adopts an analytical survey research design. The instrument of data collection for the study was a self-designed questionnaire. The findings of the study revealed that Residents of Oyo State became highly knowledgeable about gender equality through various social media platforms such as Facebook, Instagram, Twitter, YouTube, and LinkedIn, which means that they are familiar with all the necessary factors related to gender equality. Findings also highlight that Residents of Oyo State have affirmative attitudes towards gender equality. In line with the findings of this research and other studies reviewed, it is concluded that social media remains a platform that can go a long way to promote gender equality in Nigeria and the world at large. It is recommended that the Government, Non-governmental organisations, and international NGOs should tap into the opportunities by devising the use of social media, actionable programmes, and policies to promote equality between genders.